Phenolic quantification and botanical origin of Portuguese propolis - Falcão, Soraia (2014)
The production of propolis by honeybees results from a selective collection of exudates from leaf buds and plants present in the hive neighborhood leading to a resin with many potentialities in the pharmaceutical industry. This study aims to quantify the phenolic content in propolis from different Portuguese regions and in the potential floral sources, Populus x Canadensis Moench buds and Cistus ladanifer L., in order to establish links with geographical and botanical origin. The Portuguese propolis revealed a phenolic profile with marked differences in concentrations: the richness in flavonoids is common in all regions, but more evident in propolis from central interior, south and Madeira. The composition of poplar type propolis common in temperate zones was observed in the north, central coast and Azores, while the central interior and south samples, with a composition rich in kaempferol derivatives, resemble the C. ladanifer exudates, a spontaneous bush widespread in the Mediterranean. The compound kaempferol-3,7-dimethyl-ether, absent in the poplar type propolis, can be regard as a possible marker for the discrimination of these two types of propolis. (C) 2013 Elsevier B.V. All rights reserved.